Transposon insertion mapping with PIMMS – Pragmatic Insertional Mutation Mapping System - Blanchard, Adam M.; Leigh, James A.; Egan, Sharon A.; Emes, Richard D. (Frontiers in Genetics, 2015)
The PIMMS (Pragmatic Insertional Mutation Mapping System) pipeline has been developed for simple conditionally essential genome discovery experiments in bacteria. Capable of using raw sequence data files alongside a FASTA sequence of the reference genome and GFF file, PIMMS will generate a tabulated output of each coding sequence with corresponding mapped insertions accompanied with normalised results enabling streamlined analysis. This allows for a quick assay of the genome to identify conditionally essential genes on a standard desktop computer prioritising results for further investigation. Availability: The PIMMS script, manual and accompanying test data is freely available at https://github.com/ADAC-UoN/PIMMS